Bond graph aided thermal modelling of twin-tube shock absorber. (1st October 2016) - Singh, A.; Bera, T. K.
Abstract: Keeping in view the role of heat generation and dissipation, the aim of this work is to develop a thermal model for the twin-tube hydraulic shock absorber using bond graph approach. In this paper, experiment is also conducted on a rear shock absorber of a commercial passenger sedan. The temperature at the upper and lower part of the shock absorber and the force applied on the shock absorber are measured. Simulation results are compared with the experimental results to validate the model. Both the experimental and simulation results show that the volume flow rate of hydraulic fluid is more in the upper chamber than that in the lower chamber. If the surface temperature and hydraulic fluid temperature become equal, external work given to the shock absorber acts as a single entity transferring heat to the surroundings. This point marks the point of maximum heat transfer to the surroundings.